Secondary school randomized controlled interventions with a minimum dual approach to health and the links to BMI in pupils: A systematic review and meta-analysis within the project From Science 2 School - Derrick R. Tanous; Gerhard Ruedl; Mohamad Motevalli; Katharina C. Wirnitzer (Current Issues in Sport Science)
Introduction & Purpose